Economic evaluation of mechanical harvesting of lemons. (March 2018) - Brotons-Martínez, JM; Martin-Gorriz, B; Torregrosa, A; Porras, I
Several hypotheses regarding hand and mechanical harvesting have been analysed, in order to estimate the economic possibilities for the mechanical harvesting of lemons taking into account the current availability of technology. We considered several detachment options under experimental conditions; only yellow detachment has been considered for mechanical harvesting, because the sensitivity to the impacts is lower and mechanical detachment was high (80%). Price changes throughout the season were also considered. Total harvest cost is an average of the cost of mechanical harvesting (80%) and the cost of manually harvesting remaining fruit (20%), plus the cost of handling the mechanical harvested fraction. This cost ranges between 0.031 € kg −1 and 0.058 € kg −1 for outputs between 20 t ha −1 and 60 t ha −1, respectively, which is always lower than harvesting by hand (0.065 € kg −1 ). A Monte Carlo approach was used to study the sensitivity of the results, and value at risk (VaR) was calculated. The analysis showed that the mechanical harvesting margin is 0.020 € kg −1 higher than the hand harvesting margin and the output dispersion is higher in March. The VaR analysis showed that at 10%, there was no risk that the hand margin is higher than the mechanical margin and at 5%, the risk is very low and only for March harvesting. Mechanical harvesting represents a good economic option compared to hand harvesting, since it can increase farmer income by between 400 € ha −1 and 1200 € ha −1 .